The Dada Dramaturgy of Readymade Cabaret 2.0. Issue 4 (December 2021) - Edmonson, Chloë Rae
Abstract : This Is Not a Theatre Company's Readymade Cabaret 2.0 combines classic Dada dramaturgy with a Covid-era virtual theatre of short vignettes, much like the original Dada performances at the Cabaret Voltaire. Character-based dialogue strikes at the same existential questions explored by the Dada collaborators, especially prescient in the context of a global pandemic that has drastically altered our daily lives.